Synthesis and Electrochemical Characterization of rGO/CoFe2O4 Nanocomposite Material - Hoanh, Ngo Van; Tuong, Nguyen Manh; Hung, Nguyen Tran; Hieu, Le Trung; Thanh, Le Huu; Kien, Pham Trung; Hoang, Le Thanh; Thinh, Phung Xuan (VNU Journal of Science: Natural Sciences and Technology, 2023)
The rGO material was modified with CoFe 2 O 4 nanoparticles by a combination of aqueous precipitation at various pH conditions and reduction at high temperatures. The obtained rGO/CoFe 2 O 4 composite has a porous structure with a substantial surface area and pore volume. At pH 10, the synthesized composite has a specific surface area of 270 m 2 /g, and the CoFe 2 O 4 particle size is approximately 50 nm. As an electrode material in a supercapacitor system, the material has a specific capacitance of 383 F/g at a current density of 0.1 A/g, and after 1000 cycles, its specific capacitance remains at 91.5%. The obtained results demonstrate that the modification of rGO with CoFe 2 O 4 nanoparticles is an advanced and effective approach to enhancing the electrochemical properties of materials.